2011
DOI: 10.1021/pr101054m
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR-based Metabolomic Profiling in Mice Infected with Mycobacterium tuberculosis

Abstract: Tuberculosis (TB) is one of three major infectious diseases, and the control of TB is becoming more difficult because of the emergence of multidrug-resistant and extensively drug-resistant strains. In this study, we explored the (1)H NMR-based metabolomics of TB using an aerobic TB infection model. Global profiling was applied to characterize the responses of C57Bl/6 mice to an aerobic infection with virulent Mycobacterium tuberculosis (MTB). The metabolic changes in organs (i.e., the lung, the target organ of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
183
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(201 citation statements)
references
References 54 publications
12
183
6
Order By: Relevance
“…This protein was shown to partially depend on the ESX-5 secretion system for export. It would be interesting to see if secreted ALD has a complementary role to play, particularly because the relative quantities of certain amino acids, such as alanine, are found to increase in granulomatous lesions (63,64). Altogether, our findings point toward an important function of the three replicate ESAT-6 regions of ESX-5 in protein secretion and virulence of mycobacteria.…”
Section: Discussionmentioning
confidence: 78%
“…This protein was shown to partially depend on the ESX-5 secretion system for export. It would be interesting to see if secreted ALD has a complementary role to play, particularly because the relative quantities of certain amino acids, such as alanine, are found to increase in granulomatous lesions (63,64). Altogether, our findings point toward an important function of the three replicate ESAT-6 regions of ESX-5 in protein secretion and virulence of mycobacteria.…”
Section: Discussionmentioning
confidence: 78%
“…Recent studies have shown that metabolomics can be used to identify metabolites whose levels are altered in response to an infection (10,(49)(50)(51). In particular, with respect to bacterial infections, the rapid emergence of multidrug-resistant Gram-positive and Gram-negative bacteria fuels the need for novel strategies in diagnosis and treatment (11).…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Shin et al (86) detected the presence of itaconic acid in the lung tissue of M. tuberculosisinfected mice, but they hypothesized that this metabolite was synthesized by the bacteria and not by the host. Conversely, Michelucci et al (64) …”
Section: Itaconic Acid Inhibits Bacterial Growthmentioning
confidence: 99%